2018
DOI: 10.1097/jtn.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of the Translated “A Matter of Balance” Fall Prevention Program Materials for Non-English-Speaking Participants

Abstract: A Matter of Balance (MOB) is an evidence-based fall prevention program shown to reduce fear of falling (FOF) in English speaking participants. The effectiveness of translated (Chinese and Spanish) MOB materials in reducing FOF is unknown. The objective of this study was to evaluate whether MOB was associated with reduced FOF in Chinese- and Spanish-speaking participants, and included an English-speaking comparison group. Participants were recruited from MOB classes in Massachusetts and Illinois. Investigators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…This study found that an 8-week community-based Matter of Balance program improved participants' balance and strength. The Matter of Balance program has been extensively studied on reducing a participant's fear of falling through cognitive restructuring (CDC, 2019a; Sartor-Glittenberg, Bordenave, Bay, Bordenave, & Alexander, 2018; Wolfe, Arabian, Breeze, & Bugaev, 2018), but few include physical outcome measures such as balance and strength. Palmer and Mercer (2019) evaluated Matter of Balance on self-reported physical activity levels and found no effect.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that an 8-week community-based Matter of Balance program improved participants' balance and strength. The Matter of Balance program has been extensively studied on reducing a participant's fear of falling through cognitive restructuring (CDC, 2019a; Sartor-Glittenberg, Bordenave, Bay, Bordenave, & Alexander, 2018; Wolfe, Arabian, Breeze, & Bugaev, 2018), but few include physical outcome measures such as balance and strength. Palmer and Mercer (2019) evaluated Matter of Balance on self-reported physical activity levels and found no effect.…”
Section: Discussionmentioning
confidence: 99%
“…The Fall Efficacy Scale (FES), though widely used in community and long-term care settings [ 11 , 12 ], is currently not a standard tool used within the acute care setting [ 13 , 14 ]. The FES asks patients specific questions regarding their ability to complete activities with or without assistance, such as "how confident are you that you can get dressed without assistance" [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%